Barriers and facilitators influencing hearing help-seeking behaviors for adults in a peri-urban community in South Africa: a preventive audiology study - Thobekile Kutloano Mtimkulu; Katijah Khoza-Shangase; Luisa Petrocchi-Bartal (Frontiers Media S.A., 2023)
ObjectiveThis study aims to examine the barriers and facilitators to accessing ear and hearing care experienced by adults with hearing impairment in a developing South African context.MethodsA total of 23 participants were recruited through purposive sampling from an audiology department of a public hospital in peri-urban South Africa. Individual semi-structured interviews were conducted to capture a broad range of perspectives. Data were analyzed through thematic analysis.ResultsSocio-economic factors acted as the primary barrier while structural and health system factors were the main facilitator in influencing participants' journeys toward hearing help-seeking.ConclusionHelp-seeking decisions made by adults with hearing impairment are impacted by numerous factors. Individual, providers, and environmental factors combine to play a significant role in resolving ear and hearing complaints. Socio-economic and healthcare level gaps reveal the inequalities that affect help-seekers, which, therefore, need to be addressed. The provision of equitable audiology services within hearing health policy is critical for the prevention of severe consequences of hearing impairment. Plans to implement universal healthcare through the National Health Insurance (NHI) by the South African government must include the universal access to preventive audiology services.